THE IMPACT OF WEBSITE DESIGN QUALITY, SERVICE QUALITY, AND ENJOYMENT ON REPURCHASE INTENTION THROUGH SATISFACTION AND TRUST AT ZALORA - Tatang, Marko; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2017)
The advance of technology creates the new business trend by using internet. Zalora.co.id is one of the e-commerce uses website and application to deliver fashion products to the customers. The quality of website and application is the key to build the trust and satisfaction to the customers. Zalora.co.id needs a strategy to maintain the service quality and enjoyment through its website and application in order to keep and increase the customer repurchase intention on zalora.co.id.This study aims to analyze the influence of factors of repurchase intention on zalora.co.id. Website design quality, service quality and enjoyment as independent variables and repurchase intention as dependent variable. This research uses satisfaction and trust as intervening variables. Sample of this research is the application users and visitors' Zalora website in 2016 who had made a minimum of two purchases. The sampling method in this research is judgment sampling. The analysis technique used is Structural Equation Modeling – PLS. The results of this study show website design quality, service quality and enjoyment have positive effect on repurchase intention. The indirect influence of website design quality through satisfaction and trust has a negative effect.